2004
DOI: 10.1001/archotol.130.12.1374
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity of the Sinonasal Cavity

Abstract: To study the expression of important elements of the innate immune responses in human sinonasal tissue to elucidate its potential role in mucosal inflammation. Design: We studied human sinonasal tissue from patients with chronic rhinosinusitis and an immortalized epithelial cell line to detect the expression of innate immune effectors and the responses of these cells to stimulation with compounds associated with pathogenic organisms. Patients: Nine individuals undergoing endoscopic sinus surgery for chronic rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Vandermeer et al [17] demonstrated that mRNAs for TLRs were expressed in the human sinonasal mucosa of CRS and control patients using real-time PCR. Lane et al [18] showed increased levels of TLR-2 expression and a variety of inflammatory genes in the sinonasal mucosa of CRS patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Vandermeer et al [17] demonstrated that mRNAs for TLRs were expressed in the human sinonasal mucosa of CRS and control patients using real-time PCR. Lane et al [18] showed increased levels of TLR-2 expression and a variety of inflammatory genes in the sinonasal mucosa of CRS patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLR 1 through TLR10) are expressed in sinonasal epithelium [131, 132]. Signaling through TLRs results in production of cytokines and chemokines along with antimicrobial peptides.…”
Section: Host Factors and The Microbiome In Crsmentioning
confidence: 99%
“…1-4 Cathelicidins are a family of propeptides consisting of a highly conserved N-terminal sequence (cathelin) and a heterogeneous cationic and antimicrobially active C-terminal domain. 9 They are produced by monocytes and macrophages, but have also been detected in respiratory epithelia and thought to participate in nascent airway protection.…”
Section: Introductionmentioning
confidence: 99%